Medical tourism and national health care systems: an institutionalist research agenda - Daniel Béland; Amy Zarzeczny (BMC, 2018)
Abstract Although a growing body of literature has emerged to study medical tourism and address the policy challenges it creates for national health care systems, the comparative scholarship on the topic remains too limited in scope. In this article, we draw on the existing literature to discuss a comparative research agenda on medical tourism that stresses the multifaceted relationship between medical tourism and the institutional characteristics of national health care systems. On the one hand, we claim that such characteristics shape the demand for medical tourism in each country. On the other hand, the institutional characteristics of each national health care system can shape the very nature of the impact of medical tourism on that particular country. Using the examples of Canada and the United States, this article formulates a systematic institutionalist research agenda to explore these two related sides of the medical tourism-health care system nexus with a view to informing future policy work in this field.